The Effect of Group Identity on Hiring Decisions with Incomplete Information - Fortuna Casoria; Ernesto Reuben; Christina Rott (Institute of Labor Economics (IZA), 2020)
We investigate the effects of group identity on hiring decisions with adverse selection problems. We run a laboratory experiment in which employers cannot observe a worker's ability nor verify the veracity of the ability the worker claims to have. We evaluate whether sharing an identity results in employers discriminating in favor of ingroup workers, and whether it helps workers and employers overcome the adverse selection problem. We induce identities using the minimal group paradigm and study two settings: one where workers cannot change their identity and one where they can. Although sharing a common identity does not make the worker's claims more honest, employers strongly discriminate in favor of ingroup workers when identities are fixed. Discrimination cannot be explained by employers' beliefs and hence seems to be taste-based. When possible, few workers change their identity. However, the mere possibility of changing identities erodes the employers' trust towards ingroup workers and eliminates discrimination.
Keywords: J71; D91; D82; 330; discrimination; hiring; group identity; adverse selection